2013
DOI: 10.1007/s00464-013-2998-0
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endoluminal vacuum therapy is superior to other regimens in managing anastomotic leakage after esophagectomy: a comparative retrospective study

Abstract: Endoscopic endoluminal vacuum therapy was the best treatment of anastomotic leakage in systemically ill patients after esophagectomy in this retrospective analysis. It should therefore be considered an important instrument in the management of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
149
3
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(171 citation statements)
references
References 27 publications
7
149
3
12
Order By: Relevance
“…The average closure rate of these six studies was 89.2 % (91/102 patients, range 84.4-100 %) [8,10,11,[13][14][15]. Mortality rates were reported in all seven studies and the average mortality rate was 10.1 % (12/119 patients, range 0-15.6 %) [8,[10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The average closure rate of these six studies was 89.2 % (91/102 patients, range 84.4-100 %) [8,10,11,[13][14][15]. Mortality rates were reported in all seven studies and the average mortality rate was 10.1 % (12/119 patients, range 0-15.6 %) [8,[10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 89%
“…In our review of the literature we found seven major studies (case series with five or more patients) using E-Vac therapy to treat esophageal leaks and perforations [8,[10][11][12][13][14][15]. Closure rates were shown in six of the seven studies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…провели анализ различ-ных методов лечения несостоятельности анастомо-зов после хирургических операций и отметили наи-меньшую летальность -12% -в группе больных, лечившихся с применением вакуумной терапии; в группе стентированных больных летальность соста-вила 83% и в группе повторных хирургических вме-шательств -50%. В результате проведенного муль-тифакторного анализа результатов лечения авторы сделали заключение, что никакие другие клиниче-ские или лабораторные показатели, кроме характе-ра выбранного метода коррекции недостаточности анастомоза, существенно не влияли на выживае-мость пациентов [19].…”
Section: Discussionunclassified
“…Schniewind и соавт., проводя анализ различных методов лечения несостоятельности анастомозов пос-ле хирургических операций, отметили в группе ваку-умной терапии наименьшую летальность, которая составила 12 % против 83 % в группе стентирования и 50 % в группе больных, излеченных повторными хи-рургическими вмешательствами. В результате мульти-факторного анализа результатов лечения авторы заключили, что никакие другие клинические или ла-бораторные показатели, кроме выбранного метода коррекции недостаточности анастомоза, существенно не влияли на выживаемость пациентов [19].…”
Section: Discussionunclassified